2017
DOI: 10.1038/s41598-017-01006-w
|View full text |Cite|
|
Sign up to set email alerts
|

The glycogen synthase kinase MoGsk1, regulated by Mps1 MAP kinase, is required for fungal development and pathogenicity in Magnaporthe oryzae

Abstract: Magnaporthe oryzae, the causal agent of blast disease, is one of the most destructive plant pathogens, causing significant yield losses on staple crops such as rice and wheat. The fungus infects plants with a specialized cell called an appressorium, whose development is tightly regulated by MAPK signaling pathways following the activation of upstream sensors in response to environmental stimuli. Here, we show the expression of the Glycogen synthase kinase 3 (GSK3) MoGSK1 in M. oryzae is regulated by Mps1 MAP k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
(50 reference statements)
0
18
0
Order By: Relevance
“…The Ser-8 residue located in the phosphorylation motif S/ TXXXS/T (S/T represent for serine/threonine, and X can be any amino acid) that can be recognized by GSK3 (glycogen synthase kinase 3) in mammals. A GSK3 homolog, MoGsk1, was previously found to be essential for fungal development, conidiation, and pathogenicity in M. oryzae [66]. Incidentally, we also discovered this MoGsk1 as a MoHat1-interacting protein through the protein affinity purification approach (Table S2).…”
Section: Phosphorylation Of Mohat1 By Mogsk1 Is Important For Autophagy and Pathogenicitymentioning
confidence: 59%
“…The Ser-8 residue located in the phosphorylation motif S/ TXXXS/T (S/T represent for serine/threonine, and X can be any amino acid) that can be recognized by GSK3 (glycogen synthase kinase 3) in mammals. A GSK3 homolog, MoGsk1, was previously found to be essential for fungal development, conidiation, and pathogenicity in M. oryzae [66]. Incidentally, we also discovered this MoGsk1 as a MoHat1-interacting protein through the protein affinity purification approach (Table S2).…”
Section: Phosphorylation Of Mohat1 By Mogsk1 Is Important For Autophagy and Pathogenicitymentioning
confidence: 59%
“…MoCMK1 was shown playing key roles in the pathogenicity of M. oryzae , and the MoCMK1 mutants had sparse aerial hyphae, fewer conidia, and a delay in conidial germination and appressorial formation ( Liu et al, 2010 ). The expression of MoGSK1 is regulated by MPS1, another redox-modified MAP kinase, and the deletion of MoGSK1 leads to severe delay in mycelial growth, complete loss of conidiation, and inability to penetrate the host surface by mycelia-formed appressorium-like structures, thus losing the pathogenicity ( Zhou et al, 2017 ). MoSNF1 is critical for sporulation, vegetative growth, and pathogenicity of M. oryzae .…”
Section: Resultsmentioning
confidence: 99%
“…Western blot analysis showed that the phosphorylation of MoMps1 decreased by approximately 60% in the Δ Motip41 mutant. We then used qRT‐PCR to determine that expression of the CWI pathway downstream target MoGSK1 (whose expression is suppressed by MoMps1)) (Zhou et al ., 2017) was up‐regulated, whereas MoMPG1 and MoSWI6 (whose expressions are activated by MoMps1) (Penn et al ., 2015; Zhou et al ., 2017) were down‐regulated in the Δ Motip41 mutants, indicating that MoTip41 plays a positive role in modulating the CWI pathway (Fig. 8A and B).…”
Section: Resultsmentioning
confidence: 99%